Relationship between speeding and severe road accidents on the Peruvian Pan American highway - Antialon Macias, Anderson Edwin (2023)
Road accidents are an essential issue for every country in the world because their consequences are devastating for the people involved in all senses. Speeding has been considered one of the main reasons for these tragedies. Therefore, the current research analyzed the relationship between speed- ing and severe accidents on the Pan-American highway in Peru. Publicly available data kept in a Peruvian official agency was employed. Methodologically, the logit regression was harnessed since the data were categorical. After the analysis, the research found that it was riskier to have severe accidents than speeding in urban areas crossing the highway and driving or being inside a truck.